Analysis of the relation between the possession of firearms and house robbery in Brazil - Pereira da Silva Rocha , Adrian Luís; Camargos Teixeira, Evandro (Sociedad y Economía, 2025)
The persistent criminality in Brazil raises questions about the dissemination of the possession of firearms in fighting crime. Thus, this study proposes to examine the relation between the possession of firearms in residences or specific condominiums and house robbery. For this purpose, Continuous National Household Sample Survey (PNADC) data, conducted in the last quarter of 2021, were employed in addition to the estimation of a Probit model. The results revealed that the possession of firearms does not present a significant statistical relation with the probability of the people of reference in residences being victims of house robbery, indicating that the fact the resident possesses a weapon has not been effective on persuading nor repelling the criminal behavior.